Effect of Sand Addition on the Geotechnical Properties of Clay - Godwin, J.; Kwaghchimin, D. E. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2026)
Clay is commonly characterized by high plasticity, low permeability, and significant volume changes, which can result in reduced bearing capacity, excessive settlement, and instability of geotechnical structures. This study investigates the stabilization effect of sand addition on the geotechnical performance of clay for construction applications. Clay-sand mixtures containing 0% to 60% sand were prepared to evaluate Atterberg limits, soil classification, compaction behavior, unconfined compressive strength (UCS), shear strength, and hydraulic conductivity under both heavy (BSH) and light (BSL) compaction energies. The results showed that increasing sand content significantly reduces the Plasticity Index (PI) from 41.5% to 12.96%, aligning with the USCS recommended PI threshold of < 20% for suitable fill materials. Soil classification improved from CH (A-7-6) to SC (A-2 6), indicating enhanced constructability. Compaction results showed that maximum dry density increased from 1.848 to 2.17 g/cc, while optimum moisture content decreased from 16% (BSH) and 19% (BSL) to 9.6% (BSH) and 11.2% (BSL), meeting performance expectations for engineered fill. UCS increased from 120.51 kPa to 199.49 kPa, and internal friction angle rose from 8.2° to 22.3°, demonstrating greater strength and stability. In addition, hydraulic conductivity increased nearly fivefold, enhancing drainage characteristics. Overall, sand-clay mixtures with 40–60% sand content meet or approach USCS criteria for low plasticity, high density, and improved permeability, making them suitable for road embankments.